Experimental Study on Flotation of a Molybdenum Mine in Inner Mongolia by LKD-3 - Ying LI; Hong LIU; Jian WANG; Yiwen MA; Xiaojun JIANG; Qi ZHANG; Bo CUI (Kuangchan zonghe liyong, 2025)
In view of the problems of complex dissemination state, serious argillization and difficult to reduce tailings grade of a molybdenum mine in Inner Mongolia, LKD-3 collector was used to conduct the flotation test. The experimental results show that LKD-3 has good selectivity to molybdenite, and the synergistic effect of 2,3,5 - trimethylnaphthalene and carbon decanol in LKD-3 can more effectively adsorb on the surface of molybdenum minerals, enhance the hydrophobicity of molybdenum minerals, stabilize its adsorption with the reagent, and significantly improve the grade and recovery of molybdenum concentrate. Flotation test results show that the molybdenum concentrate with molybdenum grade of 53.44% and recovery of 91.79% is obtained by using LKD-3 to conduct a closed-circuit flotation test of one roughing, five cleaning and two scavenging for the raw ore with molybdenum grade of 0.164%. The grade of molybdenum concentrate increased by 6.48 percentage points and the recovery increased by 4.17 percentage points compared with the closed-circuit test using kerosene as collectors at the same process and reagent system. Research results have theoretical guiding significance and practical value for improving the production index of refractory molybdenum ore and reducing the waste of resources.